Differentiation of Mouse Stem Cells into Neural Cells on PLGAMicrospheres Scaffold: Differentiation of stem cells - Hanieh Nojehdehyan; Fatollah Moztarzadeh; Narges Zare Mehrjerdi; Hossein Baharvand (Iranian Journal of Pharmaceutical Sciences, 2007)
The cellular therapy and nerve tissue engineering will probably become a majortherapeutic strategy for promoting axonal growth through injured area in centralnervous system and peripheral nervous system in the coming years. The stem cellcarrier scaffolds in nerve tissue engineering resulted in strong survival of cells andsuitable differentiation into neural cells, so this pathway should be created afavorable environment for axon regeneration. Poly lactic-co-glycolic acid (PLGA)has been widely used for manufacturing three dimentional scaffolds for tissueengineering. The pluripotent nature and proliferative capacity of embryoniccarcinoma cells such as P19 also makes them an attractive cell source for tissueengineering. This study was initiated to evaluate potential of biodegradable PLGAmicrospheres for P19-derived neurons for neural tissue engineering and axonregeneration. The PLGAmicrospheres were prepared by using solvent evaporation,water in oil in water, technique. The water phase was polyvinyl alcohol (PVA) solutionand the oil phase was PLGAsolution. Retinoic acid (RA) was added to bacterial dishesas a differentiation factor inducer. P19 cells were attached to the PLGAmicrospheresand differentiated into neural cells on them. PLGAmicrospheres were characterisedfor size and surface morphology by scanning electron microscopy. Thein vitroexperimental studies were performed via immunoflouresent staining, scanningelectron microscopy (SEM), RT-PCR, and histology. The photomicrograph andhistology staining show the surrounded microspheres by P19 cells. The SEMresults demonstrated the attachment and axon formation. Immunoflouresent stainingand RT-PCR analysis for MapII, β-Tubulin, Nestin and Pax6 indicated the differ-entiation of P19 cells into neural cells. This report shows that high surface area alsoallows rapid cell expansion and increases cell attachment on PLGAmicrospheres,so each microsphere contains high cell density that resulted in survival of transplan-tation into the straitum of host animals, therefore, PLGAmicrospheres can help thedifferentiation of P19 cells into neural cells.